Current Biological Strategies to Enhance Surgical Treatment for Rotator Cuff Repair - Zhang, Cheng; Wu, Jun; Li, Xiang; Wang, Zejin; Lu, Weijia William; Wong, Tak-Man (Frontiers in Bioengineering and Biotechnology, 2021)
Rotator cuff tear is one of the most common shoulder problems encountered by orthopedic surgeons. Due to the slow healing process and high retear rate, rotator cuff tear has distressed millions of people all around the world every year, especially for the elderly and active athletes. This disease significantly impairs patients’ motor ability and reduces their quality of life. Besides conservative treatment, open and arthroscopic surgery contributes a lot to accelerate the healing process of rotator cuff tear. Currently, there are many emerging novel treatment methods to promote rotator cuff repair. A variety of biological stimulus has been utilized in clinical practice. Among them, platelet-rich plasma, growth factors, stem cells, and exosomes are the most popular biologics in laboratory research and clinical trials. This review will focus on the biologics of bioaugmentation methods for rotator cuff repair and tendon healing, including platelet-rich plasma, growth factors, exosomes and stem cells, etc. Relevant studies are summarized in this review and future research perspectives are introduced.